2016
DOI: 10.3389/fcimb.2016.00013
|View full text |Cite
|
Sign up to set email alerts
|

H-NS Nucleoid Protein Controls Virulence Features of Klebsiella pneumoniae by Regulating the Expression of Type 3 Pili and the Capsule Polysaccharide

Abstract: Klebsiella pneumoniae is an opportunistic pathogen causing nosocomial infections. Main virulence determinants of K. pneumoniae are pili, capsular polysaccharide, lipopolysaccharide, and siderophores. The histone-like nucleoid-structuring protein (H-NS) is a pleiotropic regulator found in several gram-negative pathogens. It has functions both as an architectural component of the nucleoid and as a global regulator of gene expression. We generated a Δhns mutant and evaluated the role of the H-NS nucleoid protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 92 publications
2
91
0
Order By: Relevance
“…Quality of RNA was assessed using a NanoDrop (ND-1000; Thermo Scientific) and a bleach 2% agarose gel as previously described (Aranda et al, 2012). qRT-PCR was performed as previously reported (Ares et al, 2016). Specific primers were designed with the Primer3Plus software 2 and are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Quality of RNA was assessed using a NanoDrop (ND-1000; Thermo Scientific) and a bleach 2% agarose gel as previously described (Aranda et al, 2012). qRT-PCR was performed as previously reported (Ares et al, 2016). Specific primers were designed with the Primer3Plus software 2 and are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Purification of RNA, and qRT-PCR were performed as previously reported (Ares et al, 2016). Briefly, DNA was removed with TURBO DNA-free (Ambion, Inc.) and the quality of RNA was assessed using a NanoDrop (ND-1000; Thermo Scientific) and a bleach agarose gel 2% as previously described (Aranda et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Adhesion to abiotic surface (polystyrene) was analyzed using 96-well plates as previously described (Ares et al, 2016). H. pylori 26695 was grown for 2 days on blood agar culture plates containing 10% defibrinated sheep blood at 37°C under microaerophilic conditions, and a bacterial suspension was prepared in Brucella broth supplemented with 10% decomplemented FBS and adjusted to an optical density of 0.1 at 600 nm.…”
Section: Methodsmentioning
confidence: 99%
“…H‐NS acts as a thermoregulator of virulence factors in several pathogenic bacteria (Falconi et al ., ; Umanski et al ., ; Ares et al ., ). We analyzed the regulatory effect of H‐NS and CRP on lngA expression at 37 and 25°C.…”
Section: Resultsmentioning
confidence: 97%
“…Our data showed that H‐NS, but not CRP, was involved in the thermoregulation of lngA , making sure that there is higher repression of Longus at lower temperatures found outside of the host (Fig. B), such as has been described in other pathogens (Falconi et al ., ; Umanski et al ., ; Ares et al ., ). Thus, it appears that CRP and H‐NS have been incorporated into the complex virulence gene regulatory networks of many bacteria to respond to nutritional and environmental stimuli, activating or repressing the expression of virulence genes (Fig.…”
Section: Discussionmentioning
confidence: 97%